Achieve the effective connection of FRP bars by blocking resistance and adhesive Force: Adhesive-Bolt hybrid joint. (1st April 2022) - Zhou, Hao; Jia, Bin; Zhang, Peng; Li, Jiajing; Huang, Hui
Abstract: The usage of Fiber Reinforced Polymer (FRP) bars for internal reinforcement has significantly increased and the connection of FRP bars has also gradually attracted attentions over the last decades. In this study, a novel connector was developed namely adhesive-bolt hybrid connector. This connector connects FRP bar effectively depending on the blocking resistance and adhesive force mainly. Based on the requirement of structure and mechanical properties, the design method of this connector was given in terms of adhesive medium, blocking bolts, sleeves. Then, the connector for FRP bar was designed and the tensile test of the joint was adjusted to verify the validity of the design method. It was found that the failure mode was the tensile destruction of FRP bar, and the stress on the sleeve was minimal at the end of the connector, while the stress on the FRP bar was minimal at the center of the connector. The effective connection of the FRP bars was realized by the adhesive-bolt hybrid connector and the excellent tensile properties of FRP bars were ensured. Finally, the bilinear bond-slip model was selected to calculate ultimate tensile capacity. The reliability of the design method was further verified by comparing the theoretical results with the experimental results of the ultimate tensile capacity.